2010
DOI: 10.1071/ah09794
|View full text |Cite
|
Sign up to set email alerts
|

The reported benefits of telehealth for rural Australians

Abstract: Rural Australians have reportedly benefited from telehealth. The reported improved access and quality of clinical care available to rural Australians through telemedicine and telehealth may contribute to decreasing the urban-rural health disparities. The reported professional development opportunities and support from specialist through the use of telehealth may contribute to improved rural medical workforces recruitment and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
302
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(313 citation statements)
references
References 40 publications
9
302
0
2
Order By: Relevance
“…[16][17][18] Telepsychiatry has been proven to be reliable and acceptable to both patients and providers for non-urgent care and has great potential for emergency care. [19][20][21][22][23][24] The initial evaluation of the MHEC-RAP during the establishment phase concluded that the program was helpful for both providers and patients. 25,26 The present study is part of a further evaluation and was designed to document longer-term changes in service use, identify gaps in services use and inform further service development.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Telepsychiatry has been proven to be reliable and acceptable to both patients and providers for non-urgent care and has great potential for emergency care. [19][20][21][22][23][24] The initial evaluation of the MHEC-RAP during the establishment phase concluded that the program was helpful for both providers and patients. 25,26 The present study is part of a further evaluation and was designed to document longer-term changes in service use, identify gaps in services use and inform further service development.…”
Section: Introductionmentioning
confidence: 99%
“…The last aspect is significant, considering minor healthcare centres which could take benefit from teleradiology implementation [20] .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the patient and the PHC worker are together at one location, while the specialist is at a remote site. Such three-way encounters can have a valuable educational role for the professionals involved, helping PHC workers increase their clinical skills and understanding of speciality areas (Wallace et al 2004) -particularly rural/regional workers (Kerr and Day 2010;Moffatt and Eley 2010) who have limited access to continuing medical education -and helping specialists develop a better understanding of front-line PHC practice.…”
Section: Significance Of Telehealth To Primary Health Carementioning
confidence: 99%